Psychiatry and empire - Mahone, Sloan, 1966-; Vaughan, Megan, 1954- (Cambridge imperial and post-colonial studies series., 2007)
Psychiatry and Empire brings together scholars in the history of medicine and colonialism to explore questions of race, gender and power relations in former colonial states across Africa, Asia, the Caribbean and the Pacific. Focusing on the intellectual histories of concepts of mental illness, mental healing and strategies of coping and resistance, this volume advances our understanding of the rise of modern psychiatry as it collided with, and sometimes underpinned, the psychology of colonial rule.